ADMINISTRATIVE-LEGAL FUNDAMENTALS OF RIGHTS IN REM TO REAL ESTATE AND THEIR ENCUMBRANCES STATE REGISTRATION UNDER MARTIAL STATE - Nikitin, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose of the paper is a comprehensive analysis of the theoretical-methodological foundations, normative foundations, and practical implementation by state registrars of Ukraine of their powers in the field of rights in rem state registration during the period of the martial state. Research methods: dialectical, systemic and comparative-legal. Results: the procedural peculiarities of registration proceedings in the field of rights in rem to real estate and their encumbrances state registration during the period of martial state were investigated, and the need to improve and overcome legal conflicts in the regulatory acts of the defined field of activity was determined. Discussion: based on a comprehensive analysis of the theoretical-legal fundamentals, normative foundations, and practical implementation by state registrars of their powers in the field of rights in rem state registration during the period of martial state, the issues of the imperfection of the normative act were identified and the emphasis was placed on possible options for improving the legislation in the defined sphere. The author provided a comprehensive analysis of the theoretical-methodological foundations, normative foundations, and practical implementation by state registrars of Ukraine of their powers in the field of rights in rem state registration during the period of the martial state. The procedural peculiarities of registration proceedings in the field of rights in rem to real estate and their encumbrances state registration during the period of martial state were investigated, and the need to improve and overcome legal conflicts in the regulatory acts of the defined field of activity was determined. Legal entities that, following the legislation of Ukraine, conduct a technical inventory, based on the results of which information is entered into the Unified State Electronic System in the field of construction, due to hostilities and annexation are unable to exercise their powers in the relevant territories, and therefore the presence of information (an identifier) regarding the technical characteristics of the real estate object in the Unified State Electronic System in the field of construction remains unregulated and, as a result, does not allow a person to apply for state registration of ownership of his/her real estate. However, the mentioned provisions contradict the general principles in the field of state registration of rights, defined by the legislation regarding the guarantee of ownership of real estate that arose before January 1, 2013, since the presence of a technical inventory and an identifier in the Unified State Electronic System in the field of construction of objects, rights registered on paper before January 1, 2013, by the legislation in force at that time, do not help a person to exercise his/her right to state registration of property rights, on the contrary, make it difficult, taking into account the legal regime of the martial state, deprive him/her of such an opportunity altogether. Based on a comprehensive analysis of the theoretical-legal fundamentals, normative foundations, and practical implementation by state registrars of their powers in the field of rights in rem state registration during the period of martial state, the issues of the imperfection of the normative act were identified, and the emphasis was placed on possible options for improving the legislation in the defined sphere.